2017
DOI: 10.4062/biomolther.2017.095
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Study of Genistein Using Solid Lipid Microparticles and Nanoparticles: Control of Oral Bioavailability by Particle Sizes

Abstract: In this study, the effect of particle size of genistein-loaded solid lipid particulate systems on drug dissolution behavior and oral bioavailability was investigated. Genistein-loaded solid lipid microparticles and nanoparticles were prepared with glyceryl palmitostearate. Except for the particle size, other properties of genistein-loaded solid lipid microparticles and nanoparticles such as particle composition and drug loading efficiency and amount were similarly controlled to mainly evaluate the effect of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…This may be attributed to the presence of a small amount of GEN in the external matrix of SLN, as previously hypothesized based on the zeta potential results. This is in disagreement with the previous work of Kim et al, which reported that GEN-loaded SLN rapidly release GEN, which could then be absorbed into the upper part of the intestine and could undergo first-pass metabolism in the liver [ 38 ]. The difference in this behaviour could be attributed to the lipid and surfactant composition affecting GEN entrapment.…”
Section: Resultscontrasting
confidence: 99%
“…This may be attributed to the presence of a small amount of GEN in the external matrix of SLN, as previously hypothesized based on the zeta potential results. This is in disagreement with the previous work of Kim et al, which reported that GEN-loaded SLN rapidly release GEN, which could then be absorbed into the upper part of the intestine and could undergo first-pass metabolism in the liver [ 38 ]. The difference in this behaviour could be attributed to the lipid and surfactant composition affecting GEN entrapment.…”
Section: Resultscontrasting
confidence: 99%
“…Smaller SLNs can be extensively absorbed in mesenteric vessels, leading to a higher absorption of the bioactive compounds rather than reaching the colon. 63 In another study, curcumin-loaded SLNs were studied for their antitumor activity through intravenous administration, and curcumin showed a 1.25 times enhanced bioavailability. 62 Other research groups compared curcumin-loaded SLNs administered via intravenous or oral routes and showed 30 or 16.4 times higher bioavailability of curcumin, respectively.…”
mentioning
confidence: 99%
“…According to the authors, this effect could be due to higher solubility and gastrointestinal release of nanomicelle-loaded genistein. The oral bioavailability was also found to be improved in genistein loaded in solid lipid nanoparticles compared to that for its suspensions or bulk powders (Kim J. T. et al, 2017). Recently, Pool et al (2018) found in studies with HT29 human colon cancer cells that incorporation of genistein into small (∼33 nm) PEGylated silica nanoparticles may substantially potentiate its antioxidant effects.…”
Section: Nano-genisteinmentioning
confidence: 98%